Utilization of Upadacitinib in the treatment of Crohn's disease: a report on two clinical cases - Quera, Rodrigo (2024)
Crohn’s disease (CD) is a chronic, progressive inflammatory disease with complications that impact the well-being of patients. The therapeutic advances achieved in recent decades, especially through the advent of biological therapy, have allowed for a transformation in the approach and management of CD, thereby modifying the course of this disease. However, a significant number of patients do not experience a satisfactory response to these drugs or lose it during the course of the disease. In this scenario, a viable alternative is to switch medications. Upadacitinib, a novel Janus  kinase inhibitor, has emerged as a promising strategy for the management of CD. We  presented two cases of patients with CD refractory to conventional therapy and biological therapy, who responded successfully to treatment with upadacitinib.